PENGARUH KREATIVITAS MENGAJAR GURU TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 6 PEKANBARU - Novrianti, Sinta; Nas, Sakdanur; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research is aimed to determine the influence of teachers creativity toward learning achievement class XI IPS on economic subjects in SMAN 6 Pekanbaru. This research was conducted in SMAN 6 Pekanbaru. The populations of this research is class XI IPS Academic Year 2015/2016 which amounted to 132 people. The samples taken with proportionate stratified random sampling method. The number of the sample was 57 people. The data analysis technique was used simple liniear regression. The results of this research indicate that: Teachers creativity influence on achievement learn student class XI IPS on economic subjects in SMAN 6 Pekanbaru.Key Words: Teachers Creativity, Learning Achievement